Evropsko (mednarodno zasebno) dedno pravo - Žnidaršič Skubic, Viktorija (Pravni letopis, 2011)
In the article authoress presents the development of European International Private Law of Succession, from its beginning, until today, when we are faced with the proposition of the Regulation of the European parliament and of the Council on jurisdiction, applicable law, recognition and enforcement of decisions and authentic instruments in matters of succession and the creation of a European Certificate of Succession. The authoress emphasizes the dilemmas of international succession as such and also presents some basic practical problems that people are faced with when involved in the procedures with an international connotation. This is followed by the explanation of suitability and also legal justification of the acceptance of the legal regulation in the field of Law of Succession by the EU. Authoress also brings up the crucial aspects of this kind of solving international inheritance problems and presents the basic solutions of the proposition of the regulation. She is explaining and also critically judging them. In the conclusion, the authoress asks herself also about the phenomenon of the so called spontaneous harmonization of the Law of Succession.
Keywords: dedno pravo; dedovanje; European private international law; evropsko mednarodno zasebno pravo; international succession; mednarodno dedovanje; mednarodno pravo; predlog uredbe o dedovanju; spontana harmonizacija dednega prava; spontaneous harmonization of law of inheritance; succession; the proposition of the regulation on succession; Trusts and estates